2(x+3)(x+3)-6x+5=0

Simple and best practice solution for 2(x+3)(x+3)-6x+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)(x+3)-6x+5=0 equation:


Simplifying
2(x + 3)(x + 3) + -6x + 5 = 0

Reorder the terms:
2(3 + x)(x + 3) + -6x + 5 = 0

Reorder the terms:
2(3 + x)(3 + x) + -6x + 5 = 0

Multiply (3 + x) * (3 + x)
2(3(3 + x) + x(3 + x)) + -6x + 5 = 0
2((3 * 3 + x * 3) + x(3 + x)) + -6x + 5 = 0
2((9 + 3x) + x(3 + x)) + -6x + 5 = 0
2(9 + 3x + (3 * x + x * x)) + -6x + 5 = 0
2(9 + 3x + (3x + x2)) + -6x + 5 = 0

Combine like terms: 3x + 3x = 6x
2(9 + 6x + x2) + -6x + 5 = 0
(9 * 2 + 6x * 2 + x2 * 2) + -6x + 5 = 0
(18 + 12x + 2x2) + -6x + 5 = 0

Reorder the terms:
18 + 5 + 12x + -6x + 2x2 = 0

Combine like terms: 18 + 5 = 23
23 + 12x + -6x + 2x2 = 0

Combine like terms: 12x + -6x = 6x
23 + 6x + 2x2 = 0

Solving
23 + 6x + 2x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
11.5 + 3x + x2 = 0

Move the constant term to the right:

Add '-11.5' to each side of the equation.
11.5 + 3x + -11.5 + x2 = 0 + -11.5

Reorder the terms:
11.5 + -11.5 + 3x + x2 = 0 + -11.5

Combine like terms: 11.5 + -11.5 = 0.0
0.0 + 3x + x2 = 0 + -11.5
3x + x2 = 0 + -11.5

Combine like terms: 0 + -11.5 = -11.5
3x + x2 = -11.5

The x term is 3x.  Take half its coefficient (1.5).
Square it (2.25) and add it to both sides.

Add '2.25' to each side of the equation.
3x + 2.25 + x2 = -11.5 + 2.25

Reorder the terms:
2.25 + 3x + x2 = -11.5 + 2.25

Combine like terms: -11.5 + 2.25 = -9.25
2.25 + 3x + x2 = -9.25

Factor a perfect square on the left side:
(x + 1.5)(x + 1.5) = -9.25

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 4x+12=x+13 | | (c+2)(c+8)=0 | | 3h+4.02=120.12 | | 2-3(x-5)=4(x-1) | | =(5x+18)(x-3) | | t^2+x^2=14 | | 3x+31=5x-27 | | -7x^2=175 | | -8x-(-3)+(-6)=4-x | | 3y-4(y-2)=10 | | 6(j+35)=132 | | 9t-9+18T=6T+12 | | -1+19m=11m+23 | | lnx=.33 | | 5-2p=-3p-5 | | .75a+4=.25(3a-16) | | 0.7(3x+4)=1.1-(x+2) | | 4(9d+2)=2(d-17)-8d | | 0.2(x+10)+0.2x=6 | | 7y=2y+10-15 | | [21-5x]=33 | | -2(5s-6)-12=-29(8s+8)-3 | | 5y-4=2y+20 | | 2z+4=5z | | 2+5(2+5)= | | 5x=12-32+x | | 4+9lnx=7 | | 7n-4=n+1 | | 3s+5(s+7)=99 | | x^2+8x+16=99 | | 114-d=83 | | 2*16= |

Equations solver categories